New urban character: Europan 10 competition in Ajka - Szabó, Árpád (4D Journal of Landscape Architecture and Garden Art, 2010)
The Hungarian site of Europan 10 highly challenged the competitors. The task to find the proper position in relation to the heritage of the socialist architecture triggered complex and socially nőt easily addressable problems.SOCIALIST EXCHANGE: let us change the architectural heritage of the former régimé and through that let us alsó affect society, States the motto of the competition site. But what are the possible strategies fór that? What are the architectural tools fór making the residents of the former socialist city to start to use their city centre? How to force them to inhabit their public spaces instead of enjoying the comfort of their vehicle?The competition entries used very different approaches, bút somé typical and characteristic issues can be pointed out.